(3eZGeQGJ GdSGMQ ZhKs - (3eUWai, gOis; (3UdGM HjUGQs ((3GdbGgQIs (3GdOGQ GdeUQjI GddHfGfjIs, 2009)
(3eLehYI bUUjI JbOe ai CSdhH jJQGhM Hjf GdNjGd hGdhGbY hJMGhd ef NdGd eG JbOeI ef bUU Cf JHjf ddfTA bjeI GdeaGgje hGdSdhcjGJ GdELJeGYjI GdeWdhHI ai EKQGA GdeLJeYGJ GdEfSGfjI hfgVJgG dCfgG JTcd GdOYGeI GdCSGSjI ai Jchjf TNUjI GdHTQs
(3GdeMJhjGJ (B: (3bUI GdSfGHd GdPgHjI(B--(3bUI Ph GdbfGY GdPgHi(B--(3bUI YOd LfOGH(B--(3bUI ZhK ai eOjfI GdYeGdbI hGdCbRGes
(3bUU TYHjIs
1 2 6 7 8 9 12 22
Keywords: Fairy Tales; (3GdbUU GdYQHjIs; (3bUU GdCWaGds; (3bUU TYHjIs